Do Daily Retail Gasoline Prices adjust Asymmetrically? - Leon Bettendorf; Stephanie van der Geest; Gerard Kuper (Tinbergen Institute, 2005)
This paper analyzes adjustments in the Dutch retail gasoline prices. We estimate an error correction model on changes in the daily retail price for gasoline (taxes excluded) for the period 1996-2004 taking care of volatility clustering by estimating an EGARCH model. It turns out the volatility process is asymmetrical: an unexpected increase in the producer price has a larger effect on the variance of the producer price than an unexpected decrease. We do not find strong evidence for amount asymmetry. However, there is a faster reaction to upward changes in spot prices than to downward changes in spot prices. This implies timing or pattern asymmetry. This asymmetry starts three days after the change in the spot price and lasts for four days.
Keywords: D43; E31; 330; Asymmetry; Retail gasoline prices; Volatility; Benzin; Preismanagement; ARCH-Modell; Schätzung; Niederlande